The determinants of exit in a developing country: core and peripheral regions - Calá, Carla Daniela (2015)
This paper analyses the regional determinants of exit in developing countries, using Argentina as an illustrative case. We find evidence of a dynamic revolving door by which past entrants increase current exits, particularly in the peripheral regions. In the central regions, current and past incumbents cause an analogous displacement effect. Also, exit shows a U-shaped relationship with respect to the informal economy, although the positive effect is weaker in the central regions. These findings point to the existence of a core-periphery structure in the spatial distribution of exits.